HUKUM TA’JIL AZ-ZAKAH KARENA ADANYA PANDEMI COVID-19 - Abadi, Khafid (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2020)
This The Ministry of Religion has issued Circular Letter No. 6 of 2020 concerning Ramadhan and Eid Al-Fitr 1 Guide Syawal 1441 H in the midst of the Covid-19 pandemic. One thing that is interesting from this Circular Letter is that in pawns 11 sub a, whose contents appeal to all Muslims to hasten the payment of zakat. From this background the question arises as follows: first how is the problem of ta'jil az-zakah in the pandemic Covid-19 seen from the proposition of the Qur'an? Secondly, how is the view of the ulama related to ta'jil az-zakah during the pandemic Covid-19? To answer this question, normative juridical approach or doctrinal law research is analytical descriptive. The results of the study note that, firstly the Qur'anic argument was not found in the verse specifically discussing ta'jil az-zakah, but permissibility of ta'jil az-zakah was included in the generality of the verse about advice to hurry the good. Secondly, there is a difference of opinion among scholars regarding ta'jil law az-zakah. The majority of scholars allow ta'jil az-zakah both zakat mal and zakat fitrah with several provisions.